Appraisal of combined agreements in BOT project finance: Focused on minimum revenue guarantee and revenue cap agreements - Jun, Jaebum (International Journal of Strategic Property Management, 2010)
Limited public funds for infrastructures have the government consider joining the private in a BOT project finance scheme. Generally, the BOT projects entail lots of managerial flexibilities that may induce the radical change of project’s cash flows, an asymmetric payoff, when facing on the uncertainties due to the BOT project finance’s unique characteristics. Among various managerial flexibilities in the BOT projects, the MRG (Minimum Revenue Guarantee) and the RCP (Revenue Cap) agreements are frequently used to protect the government and the developer from the operational risk. However, the combined effect of the MRG and RCP on the project value is not understood well because the traditional capital budgeting theory, the NPV (Net Present Value) analysis, is limited to assess the contingency of these agreements. So, the purpose of this paper is to develop the numerical model to assess the combined impact of the MRG and RCP agreements on the project value based on the option pricing theory and to suggest a theoretical framework. The approach applied in this paper is justified with the hypothetical BOT toll case and some meaningful conclusions are drawn from. The results by the option pricing concept are analyzed over those by NPV analysis and, finally, the combined value of the MRG and RCP agreements appears significant relative to the project value. First Published Online: 18 Oct 2010